Sibling Delinquency as a Risk Factor for Future Offending: An Exploratory Analysis - Walters, Glenn D. (Youth violence and juvenile justice, 2018)
Prior research has identified parents and peers as salient risk factors for delinquency. The purpose of the current investigation was to determine whether sibling delinquency might not also serve as a risk factor for future offending net the effects of parents and peers. Participants were 215 male fourth through tenth grade predominately White students from the Oregon Screening of Youth at Risk for Delinquency sample. A series of multiple linear regression analyses revealed that sibling delinquency predicted participant delinquency 5 years later, after age, prior delinquency, number of siblings, father absence, family socioeconomic status, parental monitoring, parental disciplinary style, parental acceptance, and peer delinquency were controlled. When the sample was divided into younger (age 9-12 at Wave 1) and older (age 13-17 at Wave 1) age-groups, the predictive effect of sibling delinquency was confined to the older subgroup. The results suggest that sibling delinquency may serve as a risk factor for criminal offending in adolescents who are subsequently reevaluated in emerging adulthood but not children who were subsequently reevaluated in adolescence. These findings indicate that sibling delinquency can serve as a risk factor for future offending and as a target for intervention in the treatment of delinquency.